2018
DOI: 10.6004/jnccn.2017.7202
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to the World Cancer Research Fund/American Institute for Cancer Research Guideline Is Associated With Better Health-Related Quality of Life Among Chinese Patients With Breast Cancer

Abstract: The 2007 World Cancer Research Fund/American Institute for Cancer Research (WCRF/AICR) guideline provides recommendations for cancer prevention among cancer survivors. Limited data have examined whether guideline adherence is related to health-related quality of life (HRQoL) among Chinese patients with breast cancer. An ongoing prospective cohort study involving 1,462 Chinese women with early-stage breast cancer assessed exercise, diet, and body mass index (BMI) at baseline and at 18-months follow-up after dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 40 publications
1
33
0
Order By: Relevance
“…The findings of the present study are consistent with our previous research and other observational studies [3][4][5]23,24,26,35,36]. We found that Korean breast cancer survivors with greater adherence to the ACS guidelines had higher levels of social functioning, which was assessed by a validated Korean version of the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire Core 30 (EORTC QLQ-C30) [24].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The findings of the present study are consistent with our previous research and other observational studies [3][4][5]23,24,26,35,36]. We found that Korean breast cancer survivors with greater adherence to the ACS guidelines had higher levels of social functioning, which was assessed by a validated Korean version of the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire Core 30 (EORTC QLQ-C30) [24].…”
Section: Discussionsupporting
confidence: 91%
“…In another cross-sectional study that we conducted, two dietary patterns, the healthy dietary pattern and the Western dietary pattern, were empirically derived using factor analysis among Korean breast cancer survivors, and higher healthy dietary pattern scores were associated with decreasing dyspnea and increasing insomnia scores [35]. A prospective cohort study in Hong Kong involving 1,462 Chinese breast cancer survivors investigated the association between adherence to the WCRF/AICR guidelines and HRQoL and showed that greater adherence to cancer prevention recommendations was related to higher scores for global health status, physical functioning, and role functioning, and lower scores for fatigue and pain [23]. Among elderly female breast cancer survivors in the Iowa Women's Health Study, the participants who adhered to the WCRF/AICR diet and physical activity guidelines had better physical and mental component summary scores compared to those who did not follow the guidelines [26].…”
Section: Discussionmentioning
confidence: 99%
“…HRFs inhibit successful recovery or improved wellbeing and increase mortality after diagnosis as found for cancer patients (e.g. [4,5]). To prevent and treat prevalent non-communicable diseases, abstaining from tobacco smoking, keeping body weight within the healthy range, being physically active as part of everyday life, and limiting alcohol consumption is recommended [2,[6][7][8].…”
Section: Introductionmentioning
confidence: 98%
“…The American Cancer Society's nutrition and lifestyle recommendations include, in addition to physical activity and predominantly plant-based diet, alcohol reduction or abstinence. These recommendations are also useful in the prevention of other diseases and improve the lives of cancer patients (Lei et al, 2018).…”
Section: Alcohol In Cancer Patientsmentioning
confidence: 99%